A business process reengineering framework using the analytic hierarchy process to select a traceability technology for spare parts management in capital-intensive industries - Flynn, Jared Ross (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.